Neokorporatív társadalmi-gazdasági érdekegyeztetés Közép-Európában : a szlovén modell - Zachar, Péter Krisztián (Közép-Európai Közlemények, 2011)
In his study the author deals with the question of the corporative organization of the young Slovenian state. In the first part of his writing the author presents the theory and development of corporative ideas after WWII. He sums up the main theories of Philippe C. Schmitter and Gerhard Lehmbruch, the two main thinkers of modern corporatism and shows how these theories influenced the development of societal/liberal corporatism. The author introduces the concept of concertation, the new decision-making process of the modern corporative state and differentiates it from the classic pressure politics of liberalism. After the theoretical background in the second part of his study the author gives an introspection into the forms of Slovenian corporative cooperation. First of all, he describes the main organizations of the tripartite political processes: the employers’ chambers and associations (e.g. Gospodarska zbornica Slovenije, Trgovinska zbornica Slovenije, Združenje delodajalcev Slovenije) and the employees’ unions (e.g. Zveza svobodnih sindikatov Slovenije, Konfedearcija sindikatov Slovenije Pergam, Konfederacija sindikatov 90 Slovenije). At the end of his work he shows the function of the classical corporative forums in Slovenia: the Economic and Social Council (Ekonomsko-socialni svet Slovenije, ESSS) and the National Council (Državni Svet). The author’s conclusions are unambiguous: after the successful achievement of independence and freedom, Slovenia managed to create one of the most effective organizational models of modern (societal/liberal) corporatism and uses the process of concertation fruitful for his economic stability and social welfare.